Optimizing Finite Difference Schemes for Partial Differential Equations - Naseef, Qasim Hashim (Indonesian Journal Publisher, 2025)
Effective numerical methods for solving partial differential equations (PDEs) are finite difference (FD) approaches used in many fields including heat transfer, fluid dynamics, and environmental sciences. Breaking the continuous domain in both space and time, these methods convert partial differential equations into sets of algebraic equations solvable repeatedly. The time step and grid resolution—which must be carefully selected to balance computational accuracy and efficiency—will define FD techniques. Like adaptive mesh refinement (AMR), adaptive methods dynamically alter the grid in areas of rapid solution changes to improve accuracy without adding computational expense. Especially in explicit approaches for FD, where the Courant Friedrichs Lewy (CFL) condition controls stability, it is a critical consideration. Higher stability of implicit methods results from more numerically demanding Since actual challenges frequently involve complex geometries and nonlinear dynamics, FD methods have to be modified for Multiphysics simulations with fluid-structure interactions and coupled heat-mass transfer applications. Future developments in FD techniques center on developing more efficient algorithms to manage multiscale, Multiphysics problems, therefore ensuring accuracy while lowering computer load.